Teaching material development of essay writing subject - Rulik Setiani (UAD TEFL International Conference)
This research belongs to research and development (R&D) type. The aim is to develop an essay writing teaching material for the third-semester students of the English Education Department. Essay writing is one of the compulsory subjects for the third-semester students of STKIP Muhammadiyah Kotabumi. Through an essay, students can express their ideas and thoughts. Meanwhile, good writing skills can help them to provide information more clearly to the readers. The method used in the research consists of ten steps, but the researcher limited it to seven. Those are preliminary study, data collecting, teaching material design, teaching material validation, teaching material revision, teaching material testing, and revising the teaching material product. The compiled teaching material consists of seven units. The materials refer to the course outline for the third semester of the English Education Department. The teaching material has been validated by two experts, as well as one expert for the design and one for the media. Three experts stated that the materials are in the very good category. From the trial conducted through an essay-writing test and questionnaire, it can be concluded that the teaching materials are effective to be used as the material for the subject Essay Writing. It is evident in the mean score of the 3A group, which is 74.4. Meanwhile, the questionnaire results show that three aspects of the teaching materials are in the very good category.